Central Nervous System Complaint in Worker Exposed to Air Toluene in Car Painting Workshop in Surabaya - Ukik Agustina; Jojok Mukono (JURNAL KESEHATAN LINGKUNGAN, 2017)
The existence of toluene in air work environment can affect in health worker, such as disruption of Central Nervous System (CNS), lung, kidney, eye, skin and complaint. Therefore, the aim of this research was to learn CNS complaint in workers in car painting workshop in Surabaya. The sample research was taken from total population that was appropriate with inclusion criteria. The sample total was 12 people. Air sampling was conducted by using NIOSH method number 1501 with pipe absorption material activated carbon (charcoal) that use Gas Chromatography (GC) technique. Hipurric acid was measure by NIOSH method number 8301. CNS complaint in workers was known by using Q18 questionnaire. It was standardized questionnaire to determine CNS complaint in people exposed to toluene. The result showed air toluene in painting room still in threshold level that was 18.5726 ppm. Urine hipurric acid level in painter worker showed still in threshold level with the highest urine hipurric acid in worker 0.32 g hippuric acid/g urine creatinine. It can be concluded that toluene level in air and urine hippuric acid were still in threshold level, painter workers showed a trend CNS complaint compired with administration workers. It is suggested to wear Personal Protective Equipment (PPE), such as mask for gas, gloves, glasses, special clothes and boots for working.